Myrciaria alta (Myrtaceae), a new species from Espírito Santo, Brazil - Flores, Thiago Bevilacqua; Sobral, Marcos; Valdemarin, Karinne Sampaio; Souza, Vinicius Castro (Phytotaxa, 2019)
Myrciaria (Myrtaceae) species are distributed exclusively in the New World and the genus presents its highest diversity in Brazil, particularly in the Atlantic Forest domain. Myrciaria alta, from the montane region of southeastern Brazil, is herein described, illustrated, and compared to its closest related species, Myrciaria glomerata. Moreover, data on its distribution, habitat, phenology, and conservation are provided.